2019
DOI: 10.1186/s13054-019-2435-4
|View full text |Cite
|
Sign up to set email alerts
|

Adding an orange to the banana bag: vitamin C deficiency is common in alcohol use disorders

Abstract: Background At least a third of the world’s population consumes alcohol regularly. Patients with alcohol use disorders (AUDs) are frequently hospitalized for both alcohol-related and unrelated medical conditions. It is well recognized that patients with an AUD are thiamine deficient with thiamine replacement therapy being considered the standard of care. However, the incidence of vitamin C deficiency in this patient population has been poorly defined. Methods In this ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 56 publications
1
31
0
1
Order By: Relevance
“…The recommended dietary allowance (RDA) of vitamin C for a healthy adult is 100 mg per day in Japan and 90 mg and 75 mg per day for men and women, respectively, in the United States to prevent scurvy [23]. The average concentration of ascorbate in the plasma of healthy humans is 40-60 µM [24,25]. When the plasma ascorbate concentration drops to below 11 µM, there is a risk of developing scurvy, which is thus conventionally considered deficient [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recommended dietary allowance (RDA) of vitamin C for a healthy adult is 100 mg per day in Japan and 90 mg and 75 mg per day for men and women, respectively, in the United States to prevent scurvy [23]. The average concentration of ascorbate in the plasma of healthy humans is 40-60 µM [24,25]. When the plasma ascorbate concentration drops to below 11 µM, there is a risk of developing scurvy, which is thus conventionally considered deficient [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The average concentration of ascorbate in the plasma of healthy humans is 40-60 µM [24,25]. When the plasma ascorbate concentration drops to below 11 µM, there is a risk of developing scurvy, which is thus conventionally considered deficient [24,25]. In our previous report regarding chronic obstructive pulmonary disease (COPD) and plasma ascorbate levels, we reported that plasma ascorbate levels were significantly lower in COPD patients (mean age 72.7 ± 6.9 years) than those in healthy elderly people (mean age 68.8 ± 3.8 years) using the same procedure and method as here [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, this disease is rare but continues to exist, in particular in people affected by malnutrition. It also occurs in adults and children with mental disorders, people with bad eating habits or alcoholism, and older people without medical supervision (Agarwal et al 2015;Fiorini et al 2018;Kothari et al 2020;Marik and Liggett 2019;Urueña-Palacio et al 2018). Scurvy symptoms can be linked to a total body pool of less than 300 mg and a plasma ascorbate concentration below 10 μM (EFSA NDA Panel 2013b; Institute of Medicine (US) Panel on Dietary Antioxidants and Related Compounds 2000).…”
Section: Benefits (Human Studies)mentioning
confidence: 99%
“…При алкогольном делирии, несмотря на отсутствие признаков сопутствующих заболеваний и энцефалопатии Вернике, рекомендуют введение 500 мг тиамина в течение 30 мин 1-2 раза/сут на протяжении трех дней [62,63]. Рациональным является также введение мультивитаминых препаратов [63], так как у пациентов с алкогольной зависимостью отмечается дефицит ряда витаминов [64]. При наличии признаков энцефалопатии Вернике, риск которой достаточно велик при алкогольном делирии в анамнезе [62], вводят 500 мг тиамина 3 раза/сут в течение 5 дней в сочетании с поливитаминными препаратами.…”
Section: судорогиunclassified